Clinical characteristics and prognostic factors in COVID‐19 patients aged ≥80 years. Issue 7 (9th June 2020) - Covino, Marcello; De Matteis, Giuseppe; Santoro, Michele; Sabia, Luca; Simeoni, Benedetta; Candelli, Marcello; Ojetti, Veronica; Franceschi, Francesco
Abstract : Aim: The aim of the present study was to describe the clinical presentation of patients aged ≥80 years with coronavirus disease 2019 (COVID‐19), and provide insights regarding the prognostic factors and the risk stratification in this population. Methods: This was a single‐center, retrospective, observational study, carried out in a referral center for COVID‐19 in central Italy. We reviewed the clinical records of patients consecutively admitted for confirmed COVID‐19 over a 1‐month period (1–31 March 2020). We excluded asymptomatic discharged patients. We identified risk factors for death, by a uni‐ and multivariate Cox regression analysis. To improve model fitting and hazard estimation, continuous parameters where dichotomized by using Youden's index. Results: Overall, 69 patients, aged 80–98 years, met the inclusion criteria and were included in the study cohort. The median age was 84 years (82–89 years is interquartile range); 37 patients (53.6%) were men. Globally, 14 patients (20.3%) presented a mild, 30 (43.5%) a severe and 25 (36.2%) a critical COVID‐19 disease. A total of 23 (33.3%) patients had died at 30 days' follow up. Multivariate Cox regression analysis showed that severe dementia, pO2 ≤90 at admission and lactate dehydrogenase >464 U/L were independent risk factors for death. Conclusions: The present data suggest that risk of death could be not age dependent in patients aged ≥80 years, whereas severe dementia emerged is a relevant risk factor in this population. Severe COVID‐19, as expressed by elevated lactate dehydrogenase and low oxygen saturation at emergency department admission, is associated with a rapid progression to death in these patients. Geriatr Gerontol Int 2020; : – .